The Effect of Sharia Bank Financing, Government Expenditures and Investment on Economy Growth in Indonesia - Hariandy Hasby; Sufyani HS; Norvadewi; Anizir Ali Murad; Filus Raraga (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The objectives of this study is to analyze the influence of Islamic bank financing, government expenditure, and investment on economic growth in Indonesia. These three problems can be answered by the vector autoregressive model (VAR) and the vector error correction model (VECM). VAR/VECM is a type of macro-econometrics model that is commonly used to analyze economic fluctuations. In addition, researchers also have reasons for using this method, namely because of several advantages of this method. Islamic bank financing does not have a significant effect on economic growth in Indonesia. whereas, in the long term, Islamic bank financing has a significant and negative effect on economic growth with a coefficient value of -1.111488. This shows that in the long term, changes in Islamic bank financing will always be followed by changes in GDP in the reverse direction, meaning that if there is an increase of 1% in GDP, there will be a decrease of 1.11% in Islamic bank financing. In the short term, government spending has no significant effect on economic growth in Indonesia. whereas in the long run, government spending has a positive and significant influence on economic growth in Indonesia.